Inter-hemispheric and Intra-hemispheric Transmission of Information on Bimanual and Unimanual Letter Recognition and Matching Tasks - PJ, Kumar; A, Jagadish (Journal of All India Institute of Speech and Hearing)
The purpose of the present study was to measure the time taken by normal subjects on bimanual and unimanual letter recognition and matching tasks. 30 subjects (15 males and 15 females) in the age range 19-28 years were considered for this study. 13 pairs of plastic letter cut-out of English Alphabet were used. During testing the subjects were blind-folded and were asked match and recognise the letters by feeling. All the subjects were tested in four different conditions. It was found that the sensory information transmission from right hemisphere to left hemisphere is faster than from left hemisphere to right.